Hubungan Pengetahuan Perawat Tentang NEWSS dengan Penerapannya - Fransiska Anita Ekawati; Miftahul Jannah Saleh; Alisyah Sri Astuti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
National Early Warning System Scoring (NEWSS) is a systematic approach that uses scoring to identify changes or worsening conditions of a person as well as being standardized in care so that nurses are able to determine the next step that must be done. Delay in the prevention of worsening of hospitalized patients causes the activation of code blue which can be caused by several factors, one of which is due to the lack of nurses' knowledge of NEWSS, thus affecting nurses in implementing the NEWSS protocol. This study aims to determine the relationship between nurses' knowledge about NEWSS and its application. This type of research is analytic observational with cross sectional research design. The sampling method uses probability sampling technique through proportional random sampling, amounting to 66 respondents. The instrument used was in the form of a questionnaire, the test used in this study was the chi-square statistical test, the value of p = 0.083 which was read in analysis continuity correction. This shows that p (0.083)> α (0.05) so that there is no relationship between nurses' knowledge about NEWSS and its application in the inpatient room at Swasta Hospital Makassar. It is expected that Institutions will increase supervision, so that nurses know and are able to implement the NEWSS protocol.